Hubungan Kapasitas Cadangan Kognitif dan Kualitas Hidup Lansia - Rorong, Agnes Tineke Waney; Lintuuran, Rivo Mario Warouw; Velyani, Dyani Pitra; Satyasari, Daniella; Fitriana, Ika Nur (Jurnal Locus Penelitian dan Pengabdian, 2026)
The elderly are vulnerable to geriatric problems or syndromes, including cognitive impairment that can progress to dementia, leading to a decreased quality of life. One factor that can prevent cognitive problems or impairment in the elderly is cognitive reserve capacity, the brain's ability to optimize its function and prevent damage that can affect cognition. This study aims to analyze the relationship between cognitive reserve capacity and quality of life in the elderly. A cross-sectional study was conducted on 109 elderly in Krendang Village, West Jakarta, in February 2024. Inclusion criteria included elderly aged 60-79 years who were able to read, write, and communicate in Indonesian, were in good health or had controlled medical conditions, and were able to hear and see well. The variables studied were cognitive reserve capacity (education and employment, neuroprotection, physical health risk factors, and mental health risk factors) and quality of life, as assessed by the WHOQoL-BREF instrument. Bivariate analysis was performed using the Pearson correlation test to determine the correlation between cognitive reserve capacity and quality of life. Multivariate analysis using linear regression was performed to identify factors in cognitive reserve capacity that significantly influence quality of life. A total of 109 subjects (mean age 66.2 years with a standard deviation of 4.59) participated in this study. The mean total cognitive reserve capacity score was 41.42 ± 6.79. The mean quality of life scores for the physical domain was 14.61 ± 2.41; the psychological domain 13.08 ± 1.93; the social relationships domain 13.19 ± 2.59; and the environmental domain 14.14 ± 1.97. Sociodemographic factors significantly associated with quality of life included gender, education, family residence, and financial resources. There was a significant correlation between cognitive reserve capacity and quality of life (p<0.05), with moderate correlations in the physical domain (r=0.42) and social relationships (r=0.42), and weak correlations in the psychological domain (r=0.26) and environmental domain (r=0.26). The R2 value was 14.5%. Cognitive reserve capacity is associated with quality of life in older adults, particularly in the physical domain and social relationships.